PDCT-05. FINAL RESULTS OF THE VINILO OPEN-LABEL PHASE II RANDOMIZED TRIAL FOR PEDIATRIC LOW-GRADE GLIOMAS (pLGG) COMPARING THE COMBINATION VINBLASTINE-NILOTINIB WITH VINBLASTINE ALONE. (11th November 2019) - Grill, Jacques; Brard, Caroline; Picton, Sue; Cruz, Ofelia; Schouten-vanMetteren, A Y N; Marie Sehested, Astrid; Gerber, Nicolas; Entz-Werle, Natacha; Le Deley, Marie-Cécile; Dangouloff-Ros, Volodia; Varlet, Pascale
Abstract: Chemotherapy is the mainstay of non-surgical treatment in pLGG but many patients progress again after the end of the first treatment. Apart from the standard carboplatin-vincristine, new regimens with less toxicity are therefore desirable. Single agent vinblastine is an established regimen. PDGFRA TKI inhibitors have shown efficacy in refractory pLGG as well. The VINILO phase I showed the feasibility of the combination of vinblastine with nilotinib at the expense of a 50% decrease of the dose of vinblastine. The phase II trial therefore compared vinblastine 6 mg/m2 weekly (standard arm) to vinblastine 3mg/m2 weekly plus nilotinib 230mg/m2/day. The primary endpoint was the PFS, analysed on the intention-to-treat population. The target sample size was 120 patients. Accrual was stopped after recruitment of 109 patients (53 and 56 in the vinblastine-arm and the vinblastine+nilotinib arm, respectively) between July 2016 and April 2019. Fifty-four patients had an optic pathway glioma and 45 had NF1 (these patients were allowed to enter the trial as initial therapy). Half of the patients were treated after more than one line of therapy. The planned interim analysis showed that the vinblastine+nilotinib arm was associated with a worse PFS as compared to the standard arm (HR=2.37; 95%CI, 1.26–4.46; p=0.007; with 2-year PFS of 28% versus 49%). Overall, 156 biological adverse events (AE) of grade ≥ 3 have been reported after randomization (94 in vinblastine alone arm, 62 in vinblastine+nilotinib arm) and 84 non-biological adverse events of grade ≥ 3 (50 in vinblastine alone arm, 34 in vinblastine+nilotinib arm). We conclude that the combination of vinblastine plus nilotinib was less effective than vinblastine alone, possibly because of a lower dose intensity of vinblastine in the experimental arm. Vinblastine can serve as a backbone for combinations but lowering its dose may jeopardize the efficacy.